Application of Anlotinib Combined With Neoadjuvant Chemotherapy in Primary EWS/PNET of Lung: A Case Report - Fan, YH; Ma, HX; Guo, SP; Chen, Y; Zhang, SP (Frontiers in Oncology, 2022)
Primary pulmonary EWS/PNET(PPES) is extremely rare and is associated with a poor prognosis.Tumor angiogenesis is a prominent issue in molecular targeted therapy because it plays such a crucial role in tumor growth. Anlotinib is a new oral small molecular multi-targeted receptor tyrosine kinase (RTK) inhibitor. This case study describes a 20 year-old man who has PPES. The left complete pneumonectomy was performed after four neoadjuvant chemotherapy cycles (VAC with alternating IE) combination with Anlotinib.Then, as a result, maintenance Anlotinib monotherapy was continued, with no signs of recurrence to date. To our knowledge, This is the first time Anlotinib in combination with neoadjuvant chemotherapy has been shown to be effective in PPES.